Experimental study of dynamic performance of defective cell within a PEMFC stack. (12th February 2022) - Yu, Xingzi; Zhang, Caizhi; Fan, Min; Deng, Bo; Huang, Chengcheng; Xu, Jiangfeng; Liu, Deman; Jiang, Shangfeng
Abstract: Defective cell in a PEMFC stack may reduce durability and reliability of the stack and even damage the stack. However, the dynamic performance of defective cell within a PEMFC stack is not clear. In this paper, the dynamic characteristics of the defective cell under different load conditions are analyzed. The results reveal that the defective cell has slower dynamic response rate than other single fuel cells, and the defective cell causes a poor voltage uniformity of the stack. The increased frequency of load change makes the voltage change rate of defective cell higher. The increased amplitude of load change has a more negative impact than the increased frequency of load change, and makes the defective cell more prone to flooding. Furthermore, impedance spectrum shows that these load conditions have greater negative effect for the defective cell than other cells. Finally, according to the experimental results and practical application, recommends related to control strategy of PEMFC stack are proposed to extend lifetime. Graphical abstract: Image 1 Highlights: Defective cell has slower dynamic response rate than the normal cell. Increasing amplitude of loading makes the defective cell more prone to flooding. Poor voltage uniformity of stack is proven to be caused by the defective cell. Recommends related to the control strategy are proposed to extend stack lifetime.